Transient ischemic stunning of the myocardium in stress thallium-201 gated SPET myocardial perfusion imaging: Segmental analysis of myocardial perfusion, wall motion and wall thickening changes - (:unkn) unknown (My University, 2002)
Prolonged and persistent myocardial stunning has recently been demonstrated using technetium-99m sestamibi gated single-photon emission tomography (SPET) myocardial perfusion imaging post exercise or pharmacological stress test. In this study, we investigated the early postischemic transient myocardial stunning on early and delayed poststress thallium-201 gated SPET myocardial perfusion imaging using segmental wall motion (WM) and wall thickening (WT) analysis. A total of 1,680 segments from 84 patients' studies (53 men and 31 women, mean age 60 years) were evaluated on both early and delayed thallium-201 gated SPET treadmill exercise (59) or dobutamine stress (25) myocardial perfusion imaging. Semiquantitative analysis of perfusion, WM and WT in all segments was performed by two observers. Segments were classified according to changes in WM and WT between early and delayed images into normal, fixed abnormality, or improved abnormality (transient stunning), and were further classified according to changes in perfusion into normal, fixed defects, or ischemic. There were significant correlations between perfusion and WM, perfusion and WT, and WM and WT segmental scores on both early and delayed images. Transient stunning was seen significantly (P<0.001) more often in ischemic segments than were normal or fixed perfusion defects using WM (58%) and WT (50%) assessments. There was also a significant correlation between the severity of ischemia and transient stunning with either WM (P<0.05) or WT (P<0.005) evaluation. Segmental myocardial contractility assessment from gated SPET 201Tl myocardial perfusion imaging using WM and WT was comparable, and results correlated well with the myocardial perfusion assessment. Early transient myocardial stunning was frequently observed in ischemic segments and was related to the severity of myocardial ischemia.
Keywords: Ischemic stunning; Perfusion; Thallium-201; Wall motion; Wall thickening